Building the knowledge society on the Internet : sharing and exchanging knowledge in networked environments 2026-02-15T20:44:52+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Bolisani, Ettore, 1963- (Information Science Reference, 2008)

(untitled)
"In today's networked societies, a key factor of the social and economic success is the capability to exchange, transfer, and share knowledge. This book provides research on the topic providing a foundation of an emerging and multidisciplinary field"--Provided by publisher